2022
DOI: 10.1101/2022.09.18.508380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional identification of cis-regulatory long noncoding RNAs at controlled false-discovery rates

Abstract: Long noncoding RNAs (lncRNAs) can positively and negatively regulate expression of target genes encoded in cis. However, the extent, characteristics and mechanisms of such cis-regulatory lncRNAs (cis-lncRNAs) remain obscure. Until now, they have been defined using inconsistent, ad hoc criteria that can result in false-positive predictions. Here, we introduce TransCistor, a framework for defining and identifying cis-lncRNAs based on enrichment of targets amongst proximal genes. Using transcriptome-wide perturba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that multiple lncRNA which were in proximity to neighboring protein-coding genes were known to be cis- regulating their expression (Gil & Ulitsky, 2020). This cis-regulation was either due to the escorting of TFs to the regulatory regions by the RNA molecules or the presence of DNA regulatory elements on the lncRNA loci (Yap et al, 2010; Schertzer et al, 2019; Chouvardas et al, 2022; Winkler et al, 2022). This compelled us to also look into whether the syntenic lncRNA exhibits a cis-regulatory signature that governs the expression of the neighboring genes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that multiple lncRNA which were in proximity to neighboring protein-coding genes were known to be cis- regulating their expression (Gil & Ulitsky, 2020). This cis-regulation was either due to the escorting of TFs to the regulatory regions by the RNA molecules or the presence of DNA regulatory elements on the lncRNA loci (Yap et al, 2010; Schertzer et al, 2019; Chouvardas et al, 2022; Winkler et al, 2022). This compelled us to also look into whether the syntenic lncRNA exhibits a cis-regulatory signature that governs the expression of the neighboring genes.…”
Section: Discussionmentioning
confidence: 99%